Associating liver partition and portal vein ligation versus 2-stage hepatectomy: A meta-analysis. Issue 35 (August 2018) - Shen, Yi-Nan; Guo, Cheng-Xiang; Wang, Lin-Yan; Pan, Yao; Chen, Yi-Wen; Bai, Xue-Li; Liang, Ting-Bo
Abstract: Background: The aim of this study was to conduct a meta-analysis comparing associating liver partition and portal vein ligation (ALPPS) with conventional 2-stage hepatectomy (TSH) in terms of clinical outcomes and to determine the feasibility and safety of ALPPS. Methods: A comprehensive search strategy was adopted to search the PubMed, Embase, Cochrane Library, and China Biology Medicine disc databases for studies comparing ALPPS and TSH. The search was broadened by looking up the reference lists of the retrieved articles. A meta-analysis was performed using the statistical software RevMan (v 5.3; Cochrane Collaboration). Results: A total of 7 studies involving 561 patients (ALPPS group, 136 patients; TSH group, 425 patients) were included in the present study, all of which were observational studies. Compared with TSH, ALPPS was associated with high completion rates of both stages [odds ratio (OR): 10.68, 95% confidence interval (95% CI): 3.26–34.97, P < .0001]. No significant differences were found in other outcomes such as complications of the first (OR: 4.04, 95% CI: 0.81–20.27, P = .09) and second surgical stage (OR: 1.59, 95% CI: 0.71–3.57, P = .26), liver failure (OR: 0.76, 95% CI: 0.29–1.98, P = .58) and the 90-day mortality rate (OR: 2.20, 95% CI: 1.00–4.84, P = .05). Conclusion: ALPPS is associated with lower noncompletion rate and had similar perioperative outcomes relative to TSH. However, only retrospective observational studies were included in this meta-analysis, which may have limited the strength of the evidence. High-quality, large-scale studies are required to further evaluate the outcomes of ALPPS. Abstract : Supplemental Digital Content is available in the text